Inserted Needle in the Abdominal Wall - Rahman, Md Khalliur; Sarker, AK; Islam, MB; Shahid, SMA; Haq, SMM; Khan, SR (TAJ: Journal of Teachers Association, 2009)
A 20 year old housewife presented with multiple needles in her abdominal wall as revealed by radiological examination. She had unrelated symptoms but the needles were more or less silent for months except one group caused foreign body granuloma formation. Exploration and removal of four of these needles were done under general anaesthesia. Deliberately inserted needles in the abdominal wall are very unusual, which is not yet reported to our knowledge. doi: 10.3329/taj.v15i2.3916 TAJ December 2002; Vol.15(2): 87-89